2015 Digital Heritage 2015
DOI: 10.1109/digitalheritage.2015.7413882
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the past with Google Cardboard

Abstract: Combining digital reconstruction with mobile technologies has the potential of enriching visitors experience to historic sites. Through designing a mobile App with Google Cardboard it is possible to use technology already in peoples' pockets to provide immersive on-site exploration of historic sites. This paper looks at our experience in developing such a mobile App which acts as a digital guided tour of the remains of St Andrews Cathedral. The App brings together traditional media such as audio, images, panor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 5 publications
0
14
0
2
Order By: Relevance
“…The ability to transform smart phone devices into VR headsets offer affordable and portable ways to experience VR and open a wide range of possibilities of utilising this technology to support virtual museums and experience the past [33]. It has been identified that to date, there is only a small number of museums who have managed to explore the potentials of VR, mainly due to affordability of developing and executing a virtual environment [18].…”
Section: Technical Characteristics Of Vrmentioning
confidence: 99%
“…The ability to transform smart phone devices into VR headsets offer affordable and portable ways to experience VR and open a wide range of possibilities of utilising this technology to support virtual museums and experience the past [33]. It has been identified that to date, there is only a small number of museums who have managed to explore the potentials of VR, mainly due to affordability of developing and executing a virtual environment [18].…”
Section: Technical Characteristics Of Vrmentioning
confidence: 99%
“…M oreover, the tour will be elaborated including the virtual reconstruction of the mill and the environment, so it will be possible to have some panoramic views of the area as it was in the past. In this case, the virtual tour is going to be published to use it with a simple virtual reality Head M ounted Display (HDM ) and an application for smartphone giving an immersive experience; the system employs the stereoscopy to give the illusion of depth (Fabola, 2016;M orandi et al, 2016).…”
Section: Res Ults and Future Applicationsmentioning
confidence: 99%
“…5a and Fig. 5a), as described in [2]. Audio narratives were associated with each location to serve as tour guides and additional content for the user.…”
Section: Related Work: Virtual and Augmented Reality For Learningmentioning
confidence: 99%
“…On-site exploration of heritage sites using mobile technology has also been largely discussed in the public domain. A Virtual Time Window (VTW) which facilitates on-site exploration of heritage sites using an open source virtual reality server and a mobile (tablet) client viewer is introduced in [11], [12] introduces a location-aware, Augmented Reality (AR) mobile application for exploration of a historical street, [13] discusses the use of a "serious game" for heritage learning during museum visits, and the use of Google Cardboard [18] to facilitate an on-site comparison of the past and present states of St Andrews Cathedral, armed with location-awareness and audio narratives was discussed in [2].…”
Section: Related Work: Virtual and Augmented Reality For Learningmentioning
confidence: 99%
See 1 more Smart Citation